10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
INTRODUCTION: Screening mammography contributes to reduced breast cancer mortality and is an essential preventive service. In the Department of Veterans Affairs (VA), women are the fastest-growing group enrolling in health care, yet factors that influence their screening use remain understudied. Our aim was to characterize screening mammography use among women veterans in VA primary care. METHODS: We conducted a retrospective cohort study using VA administrative data, including 374,132 women veterans aged 42-74 who were eligible for breast cancer screening and using VA primary care. The study period was July 1, 2022, to September 30, 2024. Multivariable logistic regression models estimated associations between veteran characteristics and biennial screening mammography completion. RESULTS: The screening mammography completion rate was 70%. Completion was associated with a recent women's health visit (odds ratio [OR] = 1.75; 95% confidence interval [CI]: 1.72, 1.78), any service-connected disability (OR = 1.58; 95% CI: 1.55, 1.61), and Black race (OR = 1.40; 95% CI: 1.15, 1.19). Lower completion was associated with substance-related disorder (OR = 0.67; 95% CI: 0.64, 0.69), alcohol-related disorder (OR = 0.87; 95% CI: 0.84, 0.90), and Pacific region residence (OR = 0.76; 95% CI: 0.74, 0.78). Women aged 54-62 had the highest screening odds; those aged 42-53 had the lowest across predictors. CONCLUSION: Efforts to optimize screening should target regional barriers, developing interventions for specific groups, and increasing the availability of specialized women's health training for VA.